Association between Medication Adherence, Anxiety, and Quality of Life in Pulmonary Tuberculosis Patients: A Cross-Sectional Study - Gelmeyfia; Tika Afriani; Miftahul Jannah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Tuberculosis (TB) remains a major public health problem in Indonesia with a high disease burden. Treatment success is strongly influenced by medication adherence; however, psychological factors such as anxiety and aspects of quality of life often interact in complex ways and have not been extensively examined simultaneously, particularly in primary healthcare settings. Objective: This study aimed to analyze the relationship between medication adherence, anxiety levels, and quality of life among patients with pulmonary tuberculosis. Methods: A quantitative analytic study with a cross-sectional design was conducted among 107 pulmonary TB patients using a total sampling technique. Variables were measured using standardized instruments, including the MMAS-8, GAD-7, and WHOQOL-BREF. Data were analyzed using Spearman’s rank correlation test. Results: Most respondents demonstrated a moderate level of medication adherence (62.6%), with anxiety predominantly at a minimal level (98.1%). Correlation analysis revealed a strong negative relationship between adherence and anxiety (rₛ = −0.729; p < 0.001), indicating that higher adherence is associated with lower anxiety levels. Furthermore, adherence was significantly positively associated with quality of life in the psychological (rₛ = 0.454; p < 0.001), social (rₛ = 0.461; p < 0.001), and environmental domains (rₛ = 0.600; p < 0.001), but not in the physical domain (p = 0.058). Conclusion: These findings highlight that medication adherence plays an important role not only in clinical outcomes but also in patients’ psychological well-being and quality of life. Integrating adherence-based interventions with psychosocial approaches is essential to improve treatment outcomes holistically.